Ã˜Â§Ã™â€žÃ˜Â·Ã˜Â±Ã™Å Ã™â€šÃ˜Â© Ã˜Â§Ã™â€žÃ˜Â³Ã™â€¦Ã˜Â¹Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜Â´Ã™ÂÃ™â€¡Ã™Å Ã˜Â© Ã™Ë†Ã˜Â§Ã˜Â³Ã˜ÂªÃ˜Â®Ã˜Â¯Ã˜Â§Ã™â€¦Ã™â€¡Ã˜Â§ Ã™ÂÃ™Å Ã˜ÂªÃ˜Â±Ã™â€šÃ™Å Ã˜Â© Ã™Æ’Ã™ÂÃ˜Â§Ã˜Â¡Ã˜Â© Ã˜Â§Ã™â€žÃ™Æ’Ã™â€žÃ˜Â§Ã™â€¦ - Jailani, Jailani - (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Method is an element of some important factors in learning proces for achievenent of educational goals. Learning method is a method in which the teachers as an implementer of learning activities for imparting knowledge to student. The application of this method must be appropriate with the material which can realize the goal of education. Sam’iyah syafahiyah method is a method that requires student to concern about thier skill on learning, comprohending, expressing, reading and writing. The method requires student to listen and repeat what is head in the form of arabic speech until they can speak an converse in arabic.